Meningkatkan Motivasi dan Hasil Belajar Menggunakan Metode Diskusi Pada Mata Pelajaran Matematika Materi Persamaan Linier Dua Variabel Di Kelas VIII-B SMP Negeri 2 Grogol Kabupaten Kediri - Irawan, Wawan (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this research is to increase students' understanding of the material presented, the teacher must be active in providing variations in learning, so that students do not become bored so that blocking of the material occurs. Students should have space to express their thoughts so that boredom does not occur at every meeting in learning. This research is a qualitative descriptive research with the type of Classroom Action Research which will be presented in the form of a cycle. Each cycle consists of four stages, namely (1) planning. (2) implementation or action, (3) observation, (4) reflection. The results showed that there was an increase in student motivation of (0.94) in cycle 1, from 2.56 to 3.5 in cycle 2. In increasing learning outcomes the number of students who were declared to meet the KKM standard in cycle 1 was 22 students (62 ,86%), and students who were declared to meet the KKM standard in cycle 2 were 31 students (88,57%). The percentage increase is 25.71% from cycle 1. So it can be concluded that the discussion method can improve the motivation and learning outcomes of class VIII-B students of UPTD SMP Negeri 2 Grogol on the material of Linear Equations of Two Variables.